2022
DOI: 10.1177/21582440221096661
|View full text |Cite
|
Sign up to set email alerts
|

Trade Openness, Government Consumption, and Economic Growth Nexus in Saudi Arabia: ARDL Cointegration Approach

Abstract: This study intends to examine the influence of trade openness on economic growth in the Kingdom of Saudi Arabia including government consumption and labor force as control variables. Using time-series yearly data from 1985 to 2019, the study applies the Auto-Regressive Distributed Lag (ARDL) cointegration regression and the Toda-Yamamoto (T-Y) Granger causality check to achieve the objective of the study. The ARDL model estimation discloses the positive contribution of trade openness and labor force to economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…Meanwhile, the table's findings suggest that gross capital formation, labor force, trade openness, R&D expenditure, and foreign direct investment are all indicators of GDP. These outcomes are consistent with Ntamwiza and Masengesho [90], Islam et al [91], Usman et al [92], Boeing et al [93], and Iqbal et al [94]. Furthermore, we also find that renewable energy consumption can indirectly affect economic growth via five kinds of channels.…”
Section: Indirect and Direct Economic Effects Of Renewable Energy Con...supporting
confidence: 91%
“…Meanwhile, the table's findings suggest that gross capital formation, labor force, trade openness, R&D expenditure, and foreign direct investment are all indicators of GDP. These outcomes are consistent with Ntamwiza and Masengesho [90], Islam et al [91], Usman et al [92], Boeing et al [93], and Iqbal et al [94]. Furthermore, we also find that renewable energy consumption can indirectly affect economic growth via five kinds of channels.…”
Section: Indirect and Direct Economic Effects Of Renewable Energy Con...supporting
confidence: 91%
“…It is also recommended that governments in developing nations strengthen their ability to obtain financial flows that facilitate knowledge transfers in order to increase trade-growth outcomes. Islam, Alsaif, and Alsaif (2022) examined Saudi Arabia's relationship between commercial liberalization, government consumption, and economic growth. This study used the ARDL, TY Granger casualty, unit test, diagnostic exam, and TD casualty test to span the years 1985 to 2019.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Burange et al (2019) studied the BRICS nations and found a causal relationship between trade openness and GDP growth in India, China, and South Africa, but not in Russia. M. S. Islam et al (2022) found a unidirectional relationship between government spending and trade openness in Saudi Arabia using Autoregressive Distributed Lag and Toda-Yamamoto causality tests. Studies such as those by Benarroch & Pandey (2008; suggest that the relationship between trade openness and the size of government is not very strong.…”
Section: Figure 1 Economic Complexity Rank Of Russian Versus Neighbou...mentioning
confidence: 99%